Crack field analysis by optical DIC of short cracks in Zircaloy-4 - Su, X; Wan, W; Dunne, FPE; Marrow, TJ (Elsevier, 2022)
The prediction of fatigue life is most difficult for short cracks, as their local conditions may differ from what is predicted using the remote applied loading and crack geometry. Digital image correlation (DIC) can be utilized to analyze images from an optical microscope (OM), which facilitates the local characterization of the crack field. This paper presents a Finite-Element-based approach that uses DIC-obtained displacement data to retrieve the crack field and quantify the local crack driving force. With the assumption of linear anisotropic elasticity, the change in both the Mode I and Mode II crack intensity factors over a fatigue cycle can be extracted using the interaction integral method. This allows the determination of the local driving force for short crack propagation. The application of this method is demonstrated by the full-field analysis of short fatigue cracks in blocky alpha Zircaloy-4. The sensitivity of the analysis is investigated to factors that include DIC subset size, uncertainties in crack tip position and lower quality data in the crack vicinity. This technique requires no prior knowledge of theoretical solutions or far-field boundary conditions, and it can be applied to the tip of a tortuous crack by defining an appropriate local frame of reference. The analysis is applied here to cracks under similar mode I loading that propagate on the prism plane at different rates in directions that are parallel and perpendicular to the c-axis of the hexagonal unit cell.